2015
DOI: 10.1039/c4en00151f
|View full text |Cite
|
Sign up to set email alerts
|

Exploring controls on the fate of PVP-capped silver nanoparticles in primary wastewater treatment

Abstract: What controls the fate of silver nanoparticles in primary wastewater treatment?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…For this reason, water pollution control is presently one of the major scientic research areas. 1,2 Pollutants found in textile effluents include synthetic dyes and heavy metals such as copper, chromium, and cobalt (found in metal complex dyes) which are used for dye xation in wool dyeing, as reducing agents and dye bath additives in sulphate salts. 3 Dyes are difficult to be decolorized due to their complex structure, synthetic origin and recalcitrant nature.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, water pollution control is presently one of the major scientic research areas. 1,2 Pollutants found in textile effluents include synthetic dyes and heavy metals such as copper, chromium, and cobalt (found in metal complex dyes) which are used for dye xation in wool dyeing, as reducing agents and dye bath additives in sulphate salts. 3 Dyes are difficult to be decolorized due to their complex structure, synthetic origin and recalcitrant nature.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles (NPs) have been widely applied in diverse fields, such as electronics, energy, cosmetics, , and medicine. , Among them, silver NPs (AgNPs) , have become the most commonly used, for example, in antimicrobial materials, conductive inks, , catalysts, , and flexible touch screens. However, because of the rapid growth in commercial industry and the lack of appropriate disposal protocols and treatments, AgNPs pose a daunting threat to the global environment . Exposure to AgNPs in vivo also raises concerns about biological safety.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the rapid growth in commercial industry and the lack of appropriate disposal protocols and treatments, AgNPs pose a daunting threat to the global environment. 14 Exposure to AgNPs in vivo also raises concerns about biological safety. It has been clarified that the toxicity of AgNPs originates from their degradation in lysosome with the release of Ag + ions, which can induce the formation of reactive oxygen species, trigger oxidation stress, damage DNA, and cause apoptosis of cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One study has shown that only less than 3% of silver nanoparticles spiked into the influent remain in the overflow of the primary clarifier that enters the aeration basin in a pilot-scale WRRF (Impellitteri et al 2013). Another research study has also indicated that primary wastewater treatment or sedimentation removes most silver nanoparticles (approximately 90%) to primary sludge, preventing them from moving to the secondary treatment stage (King et al 2015). In contrast, primary clarification only removed a small portion (approximately 10%) of silver nanoparticles in a lab-scale wastewater treatment utility .…”
Section: Introductionmentioning
confidence: 99%
“…62or lower, silver nanoparticles do not pose significant risks to wastewater microorganisms in full-scale WRRFs(King et al 2015).Reactor configuration, microbial functional redundancy, and microbial adaptability to silver nanoparticles are three main reasons for the proposed negligible effects of silver nanoparticles on wastewater microorganisms in full-scale WRRFs. A full-scale WRRF is connected to a sewage collection system, which steadily converts silver nanoparticles to…”
mentioning
confidence: 99%